Etiological Pattern of Dementia in Bangladesh - Khan, MRK; Rizvi, AN; Habib, MA; Hasan, MK; Mamun, A; Alam, MR; Islam, R (Bangladesh Journal of Neuroscience, 2016)
Background: Dementia is a chronic & progressive neurodegenerative disorder affecting usually older people of more than 65 years in which there are disturbances of multiple higher cortical functions including memory, thinking, orientation & others. Dementia patients are increasing in number as the population of older age group is increasing. All types of dementia are treatable, at least with psychosocial interventions. So, accurate diagnosis and evaluation of etiological pattern is essential. Methods: This cross sectional study was carried out in the Department of Neurology, Bangabandu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2012 to December 2012 on 88 patients with dementia diagnosed on the basis of mini mental state examination and DSM-IV criteria. Results: Vascular dementia was the underlying diagnosis in most of the cases (43.3 %) followed by Alzheimers Disease (20.2%) and Parkinson Disease (9%). Other causes were Mixed Dementia, Intracranial Space Occupying Lesion, Post Encephalitic, Hypoxic Encephalitic, Chronic Subdural Haematoma and Tubercular Meningitis. Conclusion: Vascular dementia is more than Alzheimer’s Dementia in Bangladesh. Multiple vascular risk factors contribute to this. Bangladesh Journal of Neuroscience 2016; Vol. 32 (2): 85-90